PENERAPAN MODEL EXPERIENTIAL LEARNING UNTUK MENINGKATKAN TANGGUNG JAWAB DAN PRESTASI BELAJAR (Studi Pada Mata Pelajaran Bahasa Indonesia Kelas VIII SMP Negeri 5 Lahat) - Rusmilawati Rusmilawati (DIADIK, 2020)
This study aims to describe the application  of experiential  learning models in class VIII of SMP Negeri  5 Lahat.  The method  used in this study is a combined  research  method  (mixed  method research) which is a combination of action research and action research. The research subjects are students  of SMP Negeri 5 Lahat in the first semester  of 2019/2020  school year. The number  of students  for the class ptk 32 people,  for the experiment  31 people,  and for the control  class 30 people. Data collection methods in this study use the assessment sheet and test results. Data analysis using score analysis and test tests consisting of different test between cycles difference test of two unrelated samples. The results showed that the application of the experimental learning model could increase responsibility and learning achievement in Indonesian VIII grade subjects at SMP Negeri 5 Lahat.